Menguak Kerentanan Gender dalam Love Scam dan Strategi Perlindungannya - Rumangga Napitupulu (Journal of Citizenship, 2025)
This study is motivated by the increasing cases of love scams in Indonesia, a form of online fraud that exploits gender vulnerabilities through emotional manipulation for financial or emotional gain. This phenomenon is exacerbated by patriarchal culture, low digital literacy, and legal limitations, with significant impacts on victims, particularly women and non-binary individuals. The research method employed is a systematic literature review of 32 national and international journals, analyzing perpetrators’ targeting patterns, victimization risk factors, and gender-based protection strategies. The findings indicate that women are the primary targets due to social pressures, patriarchal norms, and emotional needs, while non-binary individuals are vulnerable due to social isolation. Emotional manipulation, social stigma, and vulnerabilities in online dating platforms are the main factors contributing to victimization, with additional risks such as identity theft and psychological trauma. Proposed protection strategies include digital literacy education, gender-sensitive counseling, and legal reforms. The study concludes that love scams are a multidimensional phenomenon requiring an intersectional approach and cross-sectoral collaboration for early detection and effective prevention to reduce victimization and promote social justice for victims.